Dicarboxylic Acid‐Functionalized MCM‐41 with Embedded Palladium Nanoparticles as an Efficient Heterogeneous Catalyst for C–C Coupling Reactions. Issue 5 (5th February 2018) - Amini, Mostafa Mohammadpour; Mohammadkhani, Abolfazl; Bazgir, Ayoob
Abstract: Palladium nanoparticles were supported on 1, 2‐dicarboxylic acid‐functionalized MCM‐41 (Pd@DCA‐MCM) and characterized by Fourier‐transform infrared spectroscopy (FT‐IR), thermogravimetric analysis (TGA), X‐ray diffraction (XRD), atomic absorption spectroscopy (AAS), transmission electron microscopy (TEM), scanning electron microscopy (SEM), and energy‐dispersive X‐ray spectroscopy (EDS) measurements. The Pd@DCA‐MCM nanocomposite exhibited good performance as a reusable catalyst in selected coupling reactions. Abstract : Palladium nanoparticles supported on 1, 2‐dicarboxylic acid‐functionalized MCM‐41 was synthesized. The catalyst exhibited good performance as an effective heterogeneous catalyst for the Suzuki‐like, Suzuki, Hiama and Sonogashira coupling reaction. The catalyst was recovered by simple filtration and reused for several cycles without a significant loss of catalytic activity. Leaching tests, such as the hot filtration test, and AAS analysis, indicated that the catalytic reaction was primarily heterogeneous in nature.